MODERN MODELS OF INVESTMENT MANAGEMENT IN ENTERPRISES: THEORETICAL AND PRACTICAL ASPECTS - Salimova Dildora Erkinovna (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
In modern economic conditions, the sustainable development of enterprises is directly dependent on how effectively they manage investment processes. Investment management plays a crucial role not only in expanding production capacities but also in equipping enterprises with innovative technologies, increasing their competitiveness, and ensuring long-term financial stability. Today, the intensification of integration processes in the global economy, the acceleration of international capital flows, and the widespread adoption of digital technologies require the introduction of modern models and approaches to investment management in enterprises. The economy of Uzbekistan has also witnessed a sharp increase in investment activity in recent years. The creation of a favorable investment climate by the state, guarantees for foreign investors, and the expansion of public-private partnership projects have had a significant impact on enterprise performance. In this process, making investment decisions based on scientifically grounded models has become increasingly important.